Visual Metaphor, Embodied Knowledge and the Epistemological Indefinite - Connie Michele Morey (Wacana Seni Journal of Arts Discourse, 2011)
This paper argues that the epistemological experience of artistic research-representation can be understood through visual metaphor. Using Zwicky's notion of metaphor as a form of "seeing-as," the alignment of metaphor with non-truth is problematised by arguing that metaphorical understanding is experiential truth, engaged through the body-with-the-world. Visual metaphors enrich our understandings of what it means to research through art by envisioning truth as an epistemological indefinite, a form of embodied knowledge that is not halted by conclusivity but rather is expanded by a process of continual negotiation.